‘’TO CORRELATE THE DIAGNOSTIC LAPAROSCOPIC FINDINGS WITH THE CLINICAL AND RADIOLOGICAL FINDINGS IN CHRONIC ABDOMINAL PAIN PATIENTS.’’ - Dr Suvriti Chaurasia; Dr Satyam Chaurasia (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background and Objective: Chronic abdominal pain is defined as continuous or intermittent abdominal discomfort/pain lasting for more than 3 months. Diagnostic laparoscopy is an emerging tool in diagnosis of chronic non-specific abdominal pain, the diagnosis of which remains uncertain despite employing the requisite laboratory and non-invasive imaging investigations. The aim of our study was- to correlate the findings of diagnostic laparoscopy with the clinical and radiological findings. Materials and Methods: this is a prospective single centre study done in Department of Surgery of Sanjay Gandhi Memorial Hospital associated with S.S. Medical College, Rewa (M.P.) during the period of 1st June 2016 to 31st May 2017. Our study was carried out on 48 patients admitted in surgical wards. All patients having chronic abdominal pain were included in the study, and patients with acute abdominal pain, with an uncorrectable coagulopathy, or uncorrectable hypercapnia and pregnant females were excluded from the study. Detailed history, examination, baseline blood, and radiological investigations were done to reach to diagnosis. Patients were subjected to diagnostic laparoscopy, and the necessary surgical therapeutic interventions during laparoscopy were employed as per the etiology after taking informed written consent. The usefulness of laparoscopy to confirm the diagnosis and clinical management of these patients of chronic abdominal pain was evaluated. Result: Our study was carried out on 48 patients admitted in surgical wards. The incidence of chronic abdominal pain was almost equal in both genders. Peak incidence was seen in the age group of 31–40 years. Abdominal pain was present in all cases 48/48 (100%) as a chief complaint followed by abdominal distension in 17/48 (35.41%). Average duration of pain was 10.92 ± 5.88 months. 18 (37.5%) showed normal USG findings, 15 (31.25%) had dilated bowel loops and bowel thickening, 6(12.5%) had ascites, 4 (8.33%) had mesenteric lymphadenopathy, while gaseous distension was seen in 2 (4.17%). CT of abdomen was done in 11(22.9%) patients. 10(20.8%) patients showed pathological findings (ascitis, mesenteric fat thickening, lymphadenopathy, multiloculated collection, GB mass, Dilated bowel loops, pleural effusion, bowel thickening). Koch’s abdomen was the most common finding during laparoscopy followed by chronic/recurrent appendicitis. Definitive diagnosis was made in 43 patients, and 38 patients had shown resolution of pain after diagnostic laparoscopy. Conclusion: Laparoscopy offers a definitive diagnosis in a large number of patients of chronic abdominal pain and also provides therapeutic intervention. An early resort to laparoscopy can resolve the diagnostic dilemma and early treatment can be instituted.